CORRELATION BETWEEN ESTROGEN HORMONE CONCENTRATION AND ESTROUS CYCLE OF RAT FED SOYBEAN FLOUR AND TEMPEH FLOUR - Safrida, Safrida; Solihin, Dedy Duryadi; Sabri, Mustafa (Universitas Syiah Kuala, 2019)
The objective of this research was to examine the correlation between estrogen level and estrous cycle of rat fed with soybean flour and tempeh flour. A completely randomized design was applied in this study with 6 treatment groups and 5 replications. Rats in group 1, 2, and 3 were non-ovariectomized rats which were fed with pellet, 10 g soybean flour/100 g body weight/day, and 10 g tempeh flour/ 100 g body weight/day, respectively. The rats in group 4, 5, qnd 6 were ovariectomized rat which were fed with pellet, 10 g soybean flour/100 g body weight/day, and 10 g tempeh flour/100 g body weight/day, respectively. The rats were after fed with pellet, soybean and tempeh flour for 4 weeks, the estrous cycle phases of rats were examined based on the presence of vaginal epithelial cells and the number of qualitative vaginal epithelial cells, while the estrogen concentrations in serum were measured by radioimmunoassay method. The data was analyzed using analysis of variance and followed by Duncan multiple range test at 95% confidence. Non-ovariectomized rats given tempeh flour have longer estrus cycle than the non-ovariectomized rats which given soybean flour. The isoflavon contained in tempeh flour and soybean flour induced proliferation and cornification of vaginal epithelial cell. Feeding the soybean flour and tempeh flour to ovariectomized rats could optimize the estrogen hormone in initiating the estrus phase, in which of the tempeh flour addition had better effect than soybean flour. Correlation between the level of estrogen to the length of estrous cycle in both nonovariectomized rats and ovariectomized rats was positive, in which the higher the levels of estrogen the longer the length of estrous cycle.